2022
DOI: 10.26508/lsa.202101116
|View full text |Cite
|
Sign up to set email alerts
|

Topical TMPRSS2 inhibition prevents SARS-CoV-2 infection in differentiated human airway cultures

Abstract: Background: There are limited effective prophylactic/early treatments for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Viral entry requires spike protein binding to the angiotensin-converting enzyme-2 receptor and cleavage by transmembrane serine protease 2 (TMPRSS2), a cell surface serine protease. Targeting of TMPRSS2 by either androgen blockade or direct inhibition is in clinical trials in early SARS-CoV-2 infection. Methods: We used differentiated primary human airway epithelial … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…This was consistent with our preliminary experiments showing a substantial increase in infected cells at 72 h compared to 48 h, even where the initial virus dose appears to be saturating ( Figure 2B ). In the same system, we have demonstrated that the addition of camostat mesylate 24 h & 48 h after viral inoculation leads to a greatly reduced number of infected cells at 72 h 33 . This suggests that the increasing number of infected cells up to 72 h represents spread of the virus into cells that were unable to be infected by the initial inoculum (but could be infected in subsequent rounds of viral release).…”
Section: Resultsmentioning
confidence: 85%
“…This was consistent with our preliminary experiments showing a substantial increase in infected cells at 72 h compared to 48 h, even where the initial virus dose appears to be saturating ( Figure 2B ). In the same system, we have demonstrated that the addition of camostat mesylate 24 h & 48 h after viral inoculation leads to a greatly reduced number of infected cells at 72 h 33 . This suggests that the increasing number of infected cells up to 72 h represents spread of the virus into cells that were unable to be infected by the initial inoculum (but could be infected in subsequent rounds of viral release).…”
Section: Resultsmentioning
confidence: 85%
“…Based on these results, it is conceivable that primary airway epithelial cells differentiated under ALI conditions are better in-vitro modeling systems than submerged cultures for studying SARS-CoV-2 infection. Of note, while this paper was under review, a study by Guo et al (12) has been published that clearly shows (i) ACE2 and TMPRSS2 expression is significantly increased in bronchial epithelial cells differentiated under ALI conditions compared to submerged cultured cells, (ii) differentiated ALI cultures are a suitable model to investigate SARS-CoV-2 infection in the presence or absence of therapeutic drugs. Therefore, findings from both the current study and Guo's study suggest that cells differentiated under ALI conditions are physiologically relevant models for investigating SARS-CoV-2 infection.…”
Section: Figurementioning
confidence: 91%
“…Furthermore, age, sex, smoking status, and airway clinical complications have been reported to be associated with ACE2 expression in human airway epithelium (7)(8)(9). In addition, epithelial cells isolated from different parts of the airways, such as the nasal passages, bronchi, and small airways, also have different expression levels of ACE2 (10)(11)(12), which may further increase the complexity of modeling these differences with in-vitro systems.…”
Section: Introductionmentioning
confidence: 99%
“…Following exposure, SARS-CoV-2 initially replicates in the human upper airway, and ciliated bronchial epithelial cells are a major target for viral replication in the early stages of infection [1]. These cells express the viral receptor, angiotensin converting enzyme-2 (ACE-2), which is concentrated on cilia [2], and the viral entry-associated protease, transmembrane serine protease 2 (TMPRSS2) [3]. Recent studies have highlighted that variants of concern (VOC), particularly omicron, have an early replicative advantage in ciliated epithelium of the upper respiratory tract [4], with omicron replicating more rapidly, compared with delta or wild-type virus, in primary human nasal epithelial cells [5], and this variant may preferentially enter cells through the endocytic pathway, using cathepsins for viral entry [6, 7].…”
Section: Introductionmentioning
confidence: 99%